Story of food: food for thought, health, and wealth! - Sen, Benita (New Delhi The Energy Resources Institute, 2014)
Food is our basic necessity. But have you ever wondered where it comes from? Why different foods taste different? Besides answering these questions, The Story of Food also travels down the ages to give you other interesting food facts to chew on. It finds that frozen foods have been around since prehistoric times and that fast food was relished by people in ancient Rome too! Most important of all, it tells you that we get all our food from plants through a process called the food chain. So start sowing seeds today, because that is tomorrow$1 (Bs food!s
Keywords: Food